Front Cover: Thermal Decomposition of Donor‐Stabilized Phosphinoborane PH2BH2NMe3: A Tensimetry Study (Eur. J. Inorg. Chem. 35/2019). Issue 35 (16th September 2019) - Butlak, Alina V.; Kazakov, Igor V.; Stauber, Andreas; Hegen, Oliver; Scheer, Manfred; Pomogaeva, Anna V.; Timoshkin, Alexey Y.
Abstract : The Front Cover shows symbolically the thermal stability studies of the title compound. The two flasks symbolize different temperature/pressure conditions, as schematically shown by manometers and thermometers. The balance symbolizes equilibrium conditions for the vapor pressure measurements. The molecules in the upper part of the cover represent possible intermediates, studied by quantum chemical methods. Financial support from the Deutsche Forschungsgemeinschaft and St. Petersburg State University (grants Sche 384/35‐1 and SPSU 12.65.44.2017) is gratefully acknowledged. More information can be found in theFull Paper by A. Y. Timoshkin et al. For more on the story behind the cover research, see theCover Profile .